(untitled) (Estudios humanísticos. Geografía, historia y arte, 1997)
During the first half of the sixteenth century, the council of Laciana got involved in a long lawsuit against the count of Luna. The above-mentioned count was accused of a number of offences consisting in the violation of the liberties of the council and the unlawfol appropriation of their mountains. After several appeals the council lost those groundsbut; in return, they were given back many of their old privileges.